Surface Properties of Graphene and Graphene Oxide Aerogels for Energy Storage Applications - Mahmood, Rasha Shakir; Hussain, Dhia Hadi (Indonesian Journal of Chemistry, 2024)
This review is mainly on the relevance of graphene aerogels for energy storage systems highlighting their distinct properties and applications. Today, electronic devices such as smartphones, laptops, and other electrical appliances have become the axe of our daily lives. As a result, electrical energy is required for these devices. Despite the discovery of renewable energy sources as an alternative to fossil fuels, the construction of energy storage systems is still necessary to store energy. Lithium-ion batteries and supercapacitors are considered essential systems for this purpose and have witnessed tremendous development in recent years. The efficiency of these systems depends on the structure of the materials used in their formation. Graphene oxide and graphene aerogel materials improve the properties of energy storage systems in terms of stability of charging and discharging cycles, longevity, and reduction of combustion incidents resulting from ordinary compounds. However, the development of graphene aerogels faces challenges in improving their mechanical properties, the cost of their preparation, and their high agglomeration ability in solvents. Therefore, intensive efforts are needed to develop these materials for a new revolution in energy storage.